Analisa Kebutuhan Sistem Proteksi Kebakaran (Studi Kasus Gedung Science Techno Park Universitas Tribhuwana Tunggadewi) - Kune , Metusalah A.; Yurnalisdel, Yurnalisdel; Sulistyani, Kiki Frida (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Based on observations, the Science Techno Park Building of Tribhuwana Tunggadewi University requires a fire prevention system because many students use the facility for activities. Therefore, people who use the building have the potential to cause a fire. The purpose of this study is to determine the characteristics of buildings and land, analyze fire protection needs and plan the placement of fire protection equipment in the Science Techno Park Building of Tribhuwana Tunggadewi University. Literature studies, agency visits, observations, measurements, and fire safety system assessments are some examples of quantitative research and data collection methods. The fire safety system assessment includes passive and active systems. (1) The sprinklers used are upright, pendant type, and have a temperature sensitivity of 65˚C. The liquid in the tube is red in color. This finding is based on the data obtained. (2) A single water storage tank (reservoir) is used to store clean water needed daily and fire extinguishers. (3) The maximum water volume required is 494 m3, although the Groundwater Tanks (GWT) in Buildings A and B of Sains Techno Park have a capacity of 225 m3. It is recommended that hydrants and sprinklers be installed immediately in Science Techno Park buildings A and B of Tribhuwana Tunggadewi University.